Kolaborasi Pemuda dalam Meningkatkan Kesadaran Lingkungan melalui Gerakan Penghijauan di Desa Mangunharjo - Suprihandari, Miya Dewi; Lestari, Sri; Emmywati, Emmywati; Susanto, Ari; Stafrezar, Burhan; Hayati, Cucu; Sanggarwati, Diah Ayu (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2025)
Environmental awareness is one of the main challenges in creating a sustainable society. In Mangunharjo Village, low awareness of the importance of environmental conservation prompted a greening movement based on youth collaboration. This program aims to increase participation and environmental awareness through education, greening actions, and sustainable plant management. The methods used include environmental awareness training, joint tree planting, and assistance in plant maintenance. The results of the program showed an increase in youth understanding of environmental issues and increased active participation in greening activities. In addition, a synergy was created between the youth and the community in maintaining and caring for the village environment. This program has a positive impact by creating a greener environment and strengthening environmental awareness among the youth of Mangunharjo Village.